2020
DOI: 10.3389/fmed.2019.00331
|View full text |Cite
|
Sign up to set email alerts
|

Non-ionizing 405 nm Light as a Potential Bactericidal Technology for Platelet Safety: Evaluation of in vitro Bacterial Inactivation and in vivo Platelet Recovery in Severe Combined Immunodeficient Mice

Abstract: Bacterial contamination of ex vivo stored platelets is a cause of transfusion-transmitted infection. Violet-blue 405 nm light has recently demonstrated efficacy in reducing the bacterial burden in blood plasma, and its operational benefits such as non-ionizing nature, penetrability, and non-requirement for photosensitizing agents, provide a unique opportunity to develop this treatment for in situ treatment of ex vivo stored platelets as a tool for bacterial reduction. Sealed bags of platelet concentrates, seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…In conclusion, we demonstrated that the blood borne pathogen T. cruzi can be effectively inactivated by over 9.0 log 10 in PL and in PCs using 405 nm light at a dose of 270 Jcm −2 (15 mWcm −2 for 5 h) and that under these light conditions, platelets retained acceptable metabolic indices and aggregation potential. All the experimental evidences that we have accumulated so far (16,17,26), including this report, together form the basis for generating a working hypothesis that 405 nm light treatment could evolve as a simple and gentler but effective PRT system for blood component safety from bacteria, viruses and parasites, provided in-depth studies are under taken in a timely fashion to further evaluate the system.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In conclusion, we demonstrated that the blood borne pathogen T. cruzi can be effectively inactivated by over 9.0 log 10 in PL and in PCs using 405 nm light at a dose of 270 Jcm −2 (15 mWcm −2 for 5 h) and that under these light conditions, platelets retained acceptable metabolic indices and aggregation potential. All the experimental evidences that we have accumulated so far (16,17,26), including this report, together form the basis for generating a working hypothesis that 405 nm light treatment could evolve as a simple and gentler but effective PRT system for blood component safety from bacteria, viruses and parasites, provided in-depth studies are under taken in a timely fashion to further evaluate the system.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously demonstrated that violet-blue light of 405 nm wavelength alone with no added photosensitizers is effective as a bacterial inactivator (16,26); since the light wavelength is in the visible spectra, it also served as a gentle treatment for stored platelets in terms of their survival and recovery as evaluated in a SCID mouse model, while providing safety from bacteria (16). In this system, photons at 405 nm excite endogenous porphyrins (circumventing the need for an external photosensitizer) within microbial cells to a higher energy state by energy transfer; subsequent transition of electrons from the porphyrin's excited state to the ground state is accompanied with the release of toxic reactive oxygen species, including singlet oxygen molecules, which cause damage to the microbial membranes, proteins and nucleic-acids resulting in pathogen inactivation (13,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations